Does Board Size Really Matter? Evidence from Australia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
This study examines the impact of board size of Australianfirms on Tobin's Q. Agency theory suggests that there is an inverse relationship between board size and Tobin's Q (Yermack 1996